Small Business Innovation Management of Export Products and Local Government Facilitation Support (Open Society Conference, 2023)
This study aims to identify Micro Small and Medium Enterprises (MSMEs) for export products in Banyuwangi Regency, finding a management model for small business export products, identify government innovation facilities needed by MSMEs for export products, and identify policies that facilitate MSMEs innovation for Export Products. This study used descriptive qualitative method. This research attempts to dig deep into the subject matter by conducting in-depth interviews with export MSMEs actors in Banyuwangi, as well as with the Government of Banyuwangi Regency. This research found that the highest prospects for export-oriented MSMEs were in three business sectors, namely: food and beverages, handicrafts, agricultural and plantation products. The MSMEs management model begins with the constraints faced during exports, and then innovation benchmarking is carried out. Product uniqueness, quality control and delivery accuracy are also supporting elements in this model, so that there is continuity of innovation. Small businesses usually innovate based on their own initiative and according to market demand simultaneously, so it has an impact on sales turnover. Most of small businesses have used social media as a promotional media, but they rarely used the promotions platform that is provided by the local government. The government has a role in strategic policies and the use of technology, strategic policies in the banking sector, and strategic policies on export procedures. What local governments can do is optimizing the banyuwangimall.com platform, as well as provides promotional assistance by innovating media and promotional content, resulting in innovation management.